Parents providing for the needs of their adolescent child studying away from home - Abandula, Hillary Camille M.; Yeneza, Francesca Grace S.
The study aims to understand how Filipino parents portray their parental roles, provide the needs of their child studying away from home and how their adolescent child responds to these roles. Using exploratory research, fifteen (15) dyads of parents and adolescent-child respondents who are living apart from each other were asked to respond to a set of questions. The results show that both parent and child adjust to fulfill their roles as family members in order to stabilize the family dynamics. There is consistence in the responses of set of respondents. The role of parents mainly revolves around being a provider and supporter of their adolescent child. Parents try their best to provide everything their child needs, be it financial, emotional or physical. Their adolescent child in return is grateful for their parents' provision. The adolescent child's response is generally demonstrated through words and actions. Significantly, constant communication through the help of modern technology plays a very important role in maintaining their relationship.